Pengaruh Model Pembelajaran Collaborative Learning Berbantuan Media Pembelajaran Wordwall terhadap Minat Belajar Siswa pada Mata Pelajaran IPAS di Kelas IV SD Negeri 1 Kesiman Denpasar - Pratiwi, Ni Made Shintya Yuli; Triyana, I Gusti Ngurah; Wijaya, I Komang Wisnu Budi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Various research results show that many students still do not show sufficient interest in learning in the classroom learning process. One of the causes is the use of conventional learning models that are still applied by teachers. To overcome this problem, one alternative that can be taken is to apply the Collaborative Learning learning model assisted by Wordwall learning media on interest in learning science. This study aims to identify the effect of the Collaborative Learning learning model assisted by Wordwall learning media on increasing interest in learning science in grade IV students. The research method used in this study is Quasi-Experimental, with the research design namely Nonequivalent Control Group Design. The population of this study used all grade IV students of SD Negeri 1 Kesiman. Sample selection was carried out using the Non-Probability Sampling technique. So the samples in the study were grade IV A and grade IV B with a total sample size of 60 students. Research data were collected through a questionnaire consisting of 23 statement items, derived from the results of the pretest and posttest. The hypothesis was tested using an Independent Sample t-test. The Independent Sample t-test results showed that the calculated t was greater than the t table, with a value of 7.500 > 2.002. The hypothesis results showed a Sig. value (2-tailed) of 0.000 < 0.05. Therefore, it can be concluded that the Collaborative Learning model assisted by Wordwall media has an effect on students' interest in learning science in fourth-grade students at SD Negeri 1 Kesiman Denpasar.